2005
DOI: 10.1111/j.1464-5491.2005.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for stroke in Type 2 diabetic patients in Taiwan: a cross‐sectional survey of a national sample by telephone interview

Abstract: Stroke prevalence in Taiwanese T2DM is 7.5%. Diabetic patients have a higher risk of stroke than the general population, but the relative risk attenuates with age. Besides conventional atherosclerotic risk factors, stroke patients in Taiwan are characterized by lower body mass index, lower education level and residence in southern or eastern Taiwan. The negative association between body mass index and stroke in Taiwanese T2DM is in contrast to the generally accepted concept that obesity is a major risk factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 8 publications
11
31
0
Order By: Relevance
“…11,12 Taiwan is a small island, and hospitals are easily accessible by people in all parts of the island. Because patients do not need a referral to visit a doctor in a hospital and because hospitals provide better facilities and services than primary care physicians, most diabetic patients in Taiwan are cared for at hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Taiwan is a small island, and hospitals are easily accessible by people in all parts of the island. Because patients do not need a referral to visit a doctor in a hospital and because hospitals provide better facilities and services than primary care physicians, most diabetic patients in Taiwan are cared for at hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…The sample is described in detail else-where. 11,12 Of the 256 036 patients identified, a sample of 128 572 was randomly chosen, with the expectation that 70% would complete the telephone interviews.…”
Section: Methodsmentioning
confidence: 99%
“…They were explained the beneficial effects of exercise and motivated to do the same. Tseng et al (2005) and AbdulGhani et al (2005) reported that obesity leads to an increase in complication risk and the amount of the drug used in treatment with the diabetic patients and weight control is very important for the diabetic patients. While considering that 80% of the diabetic patients of Type II are over their ideal weight, it is desirable that they reduce energy consumption.The distribution of subjects according to their BMI before and after nutrition intervention in two category i.e., normal (18.5-24.99 kg/m2) and preobese(25.00-29.99 kg/m2) in group I subjects were 83.3 per cent before and after was in preobese category no change were seen, likewise the intervention were in group II 90 percent before and 86.7 (2005) per cent after was under preobese section.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] This group of patients could possibly benefit from the recommended use of ACEI/ARB. 9 However, because more than 96% of the total population of Taiwan is covered by the compulsory and universal program of the National Health Insurance since 1995, 5,6 clinical practice has to follow the guidelines and recommendations stipulated by this heath care system. The use of ACEI/ARB is restricted to the treatment of patients with hypertension or congestive heart failure, and is not able to be used as therapy for diabetic patients with increased urinary albumin excretion or for the prevention of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%